Landasan Filosofis Eksistensialisme dalam Kurikulum Merdeka Belajar - Isna Refriana; Hery Noer Aly (Departement of Mathematics Education, 2023)
Existentialism is a school of philosophy that wants the learning process to take place at the will or interest of students, and educators act as facilitators who will provide convenience to students in learning process activities. For this reason, this study aims to determine the philosophical basis of existentialism in the independent learning curriculum. This study used a qualitative research method with a library research approach. Source of data consists of primary data and secondary data. Primary data are books or scientific works related to existentialism and independent curriculum. The secondary data is everything that can support the primary data. Data is collected through observation and documentation. Data validity is done by means of triangulation. And data analysis techniques are carried out with the principles of Miles and Huberman, firstly data reduction, secondly presenting data, thirdly providing conclusions. The research results obtained show that, in the independent curriculum, the learning method used refers to the interest and talent approach. With this method, students can choose what subjects they want to learn according to their passion. Thus, this is in line with the principle of existentialism, namely freedom. Where students are given the freedom to develop themselves according to their interests and talents through the subjects they choose for themselves.